Evaluation of Functional Recovery Following Thrombectomy in Patients With Large Vessel Occlusion and Prestroke Disability - Sprügel, Maximilian; Sembill, Jochen; Kremer, Svenja; Gerner, Stefan; Knott, Michael; Hock, Stefan; Engelhorn, Tobias; Dörfler, Arnd; Huttner, Hagen; Schwab, Stefan (JAMA Network Open, 2022)
IMPORTANCE It is uncertain whether thrombectomy is associated with benefits in patients with prestroke disability.
CRIS-Team WoS Importer:2022-09-02